About one approach for monitoring of the business-processes of higher education institution - Пьянина, Светлана Ивановна (Eastern-European Journal of Enterprise Technologies, 2011)
The application of OLAP technology in business process analysis of higher education is considered in the article. The feasibility of using OLAP is considered. The implementation of OLAP into the existing information-analytical system is considered